Two new species of Oocyclus (Coleoptera: Hydrophilidae) from Colombia - GARCÍA-HERNÁNDEZ, ANDREA LORENA (Revista Colombiana de Entomología, 2009)
Two new species of the genus Oocyclus (O. luteus sp. n and O. morgani sp. n.) are described from the department of Quindío, Colombia. The first report of the genus for Colombia is made, and the diagnostic characters and male genitalia are illustrated.